Implementation of Pancasila Values through the Local Wisdom of Nompudu Valaa Mpuse in the Kaili Community - Unzila Unzila; Taufiq Eka Riandhana (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Civic Education requires efforts to internalize Pancasila values through local wisdom that lives within society. One form of such local wisdom is the Nompudu Valaa Mpuse tradition practiced by the Kaili community, which has recently begun to experience shifts due to the influence of modernization. This study aims to describe the implementation of Pancasila values through the Nompudu Valaa Mpuse tradition as an effort to strengthen Civic Education. This research employed a qualitative approach with a descriptive research design. The research informants consisted of traditional leaders, community members, Kaili cultural observers, and the younger generation within the Kaili community, selected using purposive sampling techniques. The research instruments included observation guidelines, semi-structured interviews, and documentation. Data analysis was conducted cyclically through the stages of data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure data validity. The results indicate that the Nompudu Valaa Mpuse tradition embodies the values of Pancasila, including the value of divinity reflected through prayers and expressions of gratitude, the value of humanity manifested in the spirit of mutual cooperation, the value of unity reflected in community togetherness, the value of democracy represented through deliberation, and the value of social justice demonstrated through the equal distribution of assistance. This tradition also contains cultural symbols, cultural identity, implementation processes, and meanings that are passed down from generation to generation within the Kaili community. Therefore, the Nompudu Valaa Mpuse tradition is recommended to be integrated into Civic Education learning as an effort to preserve culture while strengthening character based on Pancasila values.